Perencanaan Lanskap Saluran Irigasi “Tukad Tanah Putih” di Desa Adat Tegal Darmasaba, Kabupaten Badung sebagai Kawasan Rekreasi - Paradista, Gusti Ayu Made Tasya; Asmiwyati, I Gusti Agung Ayu Rai; Sudana, I Putu (Jurnal Arsitektur Lansekap; Vol. 10, No. 2 Oktober 2024DO - 10.24843/JAL.2024.v10.i02.p03, 2024)
The development of river areas can be planned by utilizing the river as a recreation area. Planning development is carried out by utilizing the potentials that exist in the river area, one of the rivers that can be developed its potential is the Tukad Tanah Putih which is located and crosses Badung Regency, Bali. The Tukad Tanah Putih area is an area that is often visited by local people for recreational activities and daily activities, but current conditions are not good in structuring and developing the area such as the unavailability of facilities and infrastructure in the area resulting in damage to physical conditions that make not comfortable in the area for recreation. The Tukad Tanah Putih area is planned as a recreation area that is in harmony with nature and is able to accommodate the community for recreation, with planning space zoning in adapted to the results of regional analysis and synthesis. The research method has been carried out using a survey method with observation, documentation, interviews, and library studies with the stages of inventory, analysis, synthesis, and landscape planning with the aspects studied are biophysical and social aspects. Regional planning resulted in the division of zones, namely active recreation zone, passive recreation zone, and a visual zone, with conservation vegetation and aesthetic vegetation, and planned includes primary circulation and secondary circulation. The results of this study are in the form of recommendations for Tukad Tanah Putih as a recreation area with site plan and ilustrations for each area.